Effect of addition of a starter cultures on physicochemical and sensory properties of “alheira”, a smoked sausage-like product - Diana Brito Barros; Cristina Sobrosa; Rita Pinheiro; Susana Fonseca; Manuela Vaz-Velho (Millenium, 2018)
Introduction: “Alheira” is a traditional Portuguese smoked sausage-like product that can be manufactured with different types of meat and bread. Biopreservation of foods has gained special prominence due to the possibility of naturally controlling the growth of pathogenic and spoilage microorganisms, with a growing interest in the use of lactic acid bacteria (LAB) and their bacteriocins.